2012
DOI: 10.1093/geront/gns107
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation of Racial Disparities in Mental Health Service Use Among Older Adults

Abstract: The findings suggest that improving the access to mental health care in certain regions, the South in particular, may be essential to reduce racial disparities at the national level. Policy implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…Also, women were more likely to have an unmet need for mental health treatment or counselling in comparison to men 15. Women might be more susceptible to a lack of mental health services within high-income inequality states 16 17…”
Section: Introductionmentioning
confidence: 99%
“…Also, women were more likely to have an unmet need for mental health treatment or counselling in comparison to men 15. Women might be more susceptible to a lack of mental health services within high-income inequality states 16 17…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] In fact, models of health care utilization have included geographic factors since the 1960s. 31,32 A patient's geographic location is not only associated with access to and utilization of services, 30,33,34 but also with outcomes of care. 35 However, despite the multitude of documented health disparities associated with unmet need for behavioral health services [1][2][3][4][5][6][7] and the growing body of evidence supporting integrated primary care, [19][20][21][22][23] little is known about disparities in access to integrated care.…”
mentioning
confidence: 99%
“…Disparities in mental health care between racial-ethnic minority and non-minority groups in the United States have been well documented. Previous research consistently suggests that people in racial-ethnic minority groups tend to underutilize mental health services compared with non-Hispanic whites (1–7). However, racial-ethnic differences in regard to mental health problems do not always indicate greater need for such services among racial-ethnic minority groups (813).…”
mentioning
confidence: 99%
“…According to Andersen’s (18,19) behavioral model of health service utilization, which is the conceptual framework of this study, individuals’ health care access is influenced not only by person-level factors (predisposing, enabling, and health need factors), but also by community-level factors, including geographic location and geographic characteristics. Research suggests the important role of geography in mental health care (20–22), as well as in mental health service use (7,2325). In a study of adults in 13 states, Ayers and colleagues (25) identified geographic variations in need for mental health services, mental health service use, unmet need for mental health services, overuse of mental health services, and intensity of mental health services.…”
mentioning
confidence: 99%
See 1 more Smart Citation